Madrasah: dari Nizamiyyah hingga Pesisiran Jawa - Junaedi, Mahfud (Nadwa, 2014)
Growth and development in the Coastal Java madrasah in the early twentieth cen-tury until now generally spearheaded by scholars/religious leaders who graduated in Islamic centers in the Middle East. At first they established the boarding school, followed by the establishment of madrasah to the coast of Java can be regarded as children of a boarding school. The educational institutions have bonding formation of madrasah was first built by Niz{am al-Mulk in Baghdad in 1057, later known as madrasah Niz{amiyah. This school is an educational institution that aims to teach Fiqh Sunni schools. Institutions of higher education has become one of the eleventh century and became the blueprint for the development of similar madrasah in the Islamic world. Historically, madrasah in Java can not be separated from the Middle East, especially the relationship Haramayn scholars of al-Azhar and Cairo with the students in Java, Indonesia.